The Secreted Ribonuclease SRE1 Contributes to Setosphaeria turcica Virulence and Activates Plant Immunity - He, Shidao; Huang, Yufei; Sun, Yanqiu; Liu, Bo; Wang, Suna; Xuan, Yuanhu; Gao, Zenggui (Frontiers in Microbiology, 2022)
During the plant infection process, pathogens can secrete several effectors. Some of the effectors are well-known for their roles in regulating plant immunity and promoting successful pathogen colonization. However, there are few studies on the ribonuclease (RNase) effectors secreted by fungi. In the present study, we discovered a secretable RNase (SRE1) in the secretome of Setosphaeria turcica that was significantly upregulated during the early stages of S. turcica infection in maize. Knockdown of SRE1 significantly reduced the virulence of S. turcica. SRE1 can induce cell death in maize and Nicotiana benthamiana. However, unlike the conventional hypersensitive response (HR) caused by other effectors, SRE1 is not dependent on its signal peptide (SP) or plant receptor kinases (such as BAK1 and SOBIR1). SRE1-induced cell death depends upon its enzymatic activity and the N-terminal β-hairpin structure. SRE1 relies on its N-terminal β-hairpin structure to enter cells, and then degrades plant's RNA through its catalytic activity causing cytotoxic effects. Additionally, SRE1 enhances N. benthamiana's resistance to pathogenic fungi and oomycetes. In summary, SRE1 promotes the virulence of S. turcica, inducing plant cell death and activating plant immune responses.